Psychological factors influencing emotional reactions to gestational trophoblastic disease: The role of coping mechanisms and illness perception. (18th January 2021) - Di Mattei, Valentina; Mazzetti, Martina; Perego, Gaia; Cugnata, Federica; Brombin, Chiara; Bergamini, Alice; Cioffi, Raffaella; Vasta, Francesca; Pella, Francesca; Rabaiotti, Emanuela; Mangili, Giorgia; Candiani, Massimo
Abstract: Objective: Referring to Leventhal's common‐sense model, this observational cross‐sectional study aimed at investigating the relationship between illness mental representations, coping mechanisms and psychological distress in a sample of women with gestational trophoblastic disease (GTD). Methods: Thirty‐eight women diagnosed with GTD (18 with hydatidiform mole; 20 with gestational trophoblastic neoplasia) were asked to complete the Illness Perception Questionnaire—Revised, the Coping Orientation to the Problems Experienced, the State‐Trait Anxiety Inventory—Form Y and the Beck Depression Inventory—Short Form. Demographic and clinical information was collected through a self‐report questionnaire. Results: The sample did not report significant symptomatic distress in relation to GTD. Correlation analysis showed that the Emotional representations subscale of the Illness Perception Questionnaire—Revised was significantly associated with both state anxiety and depression; avoidant coping significantly and positively correlated with anxiety and depression, as well as with illness emotional representations. Mediation analysis revealed significant indirect effects of avoidant coping on both anxiety and depression through the mediation of emotional representations. Conclusion: Avoidant coping could lead women to develop emotional representations of illness characterised by negative affects, which in turn enhance distress levels. Results underline the importance to promote adaptive coping strategies, along with accurate illness perceptions, to foster better psychological adjustment to GTD.